Factors associated with hypoacusia induced by noise in workers of a metalmechanical company of Talara, Piura. Period 2015 – 2018 - Cerro-Romero, Shirley M. (2020)
Introduction: Hearing loss is a frequent occupational disease and causes deterioration in the quality of life of workers. Objetive: The objective was to identify the prevalence and factors associated with noise-induced hearing loss in workers of a metalworking company. Material and Methods: Analytical cross-sectional study. Data from occupational medical records were used to determine the frequency of hearing loss due to noise and its potential associated factors (age, sex, personal history). Simple and multiple regression models were constructed, estimating prevalence ratios (RP) using generalized linear models, Poisson family and log link function. Results: Of 1543 workers, the average age was 36.7 years and the majority were male (93.6%). Only 8.2% reported illness and / or occupational accident prior to the occupational evaluation. 10.7% had hearing loss due to noise. The frequency of presenting hearing loss increased 10% for each additional year of age (PR = 1.10, 95% CI: 1.09-1.12, p <0.001) and having a history of illness / work accident increased 75% the frequency of presenting hearing loss (RP = 1.75, 95% CI: 1.28-2.40, p <0.001). Conclusion: The prevalence of hearing loss due to noise was low. Age in years and the history of illness / accident were positively associated with hearing loss. It is suggested that annual audiometry follow-up be carried out, with special emphasis on the occupational history associated with hearing loss due to noise.